Short Communication: Analysis of the ultimate wood composition of a forest plantation species, Eucalyptus pellita, to estimate its bioelectricity potency - MUHAMMAD TAUFIQ HAQIQI; DUDU HUDAYA; HELMI ALFATH SEPTIANA; RICO RAMADHAN; YULIANSYAH YULIANSYAH; WIWIN SUWINARTI; RUDIANTO AMIRTA (Society for Indonesian Biodiversity, 2022)
Abstract. Haqiqi MT, Hudaya D, Septiana HA, Ramadhan R, Yuliansyah, Suwinarti W, Amirta R. 2022. Short Communicarion: Analysis of the ultimate wood composition of a forest plantation species, Eucalyptus pellita, to estimate its bioelectricity potency. Biodiversitas 23: 2389-2394. Eucalyptus pellita F. Muell is one of the short rotation wood crop species widely planted in tropical countries, including Indonesia. Woody biomass obtained from this species is commonly utilized to produce fiber in the pulp and paper industry. Due to the growing interest in expanding E. pellita plantations, the potential application of E. pellita woody biomass to provide sustainable energy feedstock has been studied. Therefore, this study aimed to investigate the ultimate composition of E. pellita wood (carbon (C), hydrogen (H), and oxygen (O)) to estimate its higher heating value (HHV) and bioelectricity potency. The wood samples were harvested at different plant ages, from the first to the fifth year. The percentage of biomass composition, including cellulose, hemicellulose, lignin, and extractives, was also calculated. The results demonstrated that lignin in the E. pellita wood increased to align with the increased plant age. Thus, this pattern was followed by significantly increased C content in the wood since lignin contained a primary source of C. Hence, this condition might enhance the HHV and electricity potency. The ratio of H/C and O/C was found to be one of the most promising factors in improving HHV compared to the extractive/lignin ratio. In the fifth year, the electricity potency of E. pellita showed the highest value (1.71 MWh ton-1). Therefore, this study suggests that E. pellita possesses the potential to be one of the promising crops for green electricity production.